Student Errors in Mathematics Word Problem: What Can Be Learned? - Adri Nofrianto; Albert D.C. Gulo; Mira Amelia Amri; Elfa Rafulta (Universitas Maritim Raja Ali Haji, 2022)
This study aims to understand better student errors in solving mathematics word problems. A Word problem is a problem that has a story or arrangement based on sentences. The qualitative research approach was used. The data were collected by giving tests and interviewing two male high achievers senior high school students in mathematics. The student error analysis adopted the Newman error analysis system. The source triangulation was used to ensure the data validity. Based on the collecting data and data analysis, the decoding/reading error happened caused by students' common understanding or unfamiliarity of the mathematical terms used in the problem. The subjects showed inconsistency in interpreting problem sentences and misused mathematical symbols. Furthermore, the subject encountered difficulties with the arithmetic process, especially fractions and their operation. This research identified students' difficulties in solving problem mathematics word problems. Moreover, this research provides evidence that encourages further research on mathematical literacy, mathematical communication skills, students' arithmetic skills, and the evaluation process of the problem-solving activity.